SAPPHIRINE-BEARING SILICA-UNDERSATURATED GRANULITES FROM FOREFINGER POINT, ENDERBY LAND, EAST ANTARCTICA : EVIDENCE FOR A CLOCKWISE P-T PATH? - モトヨシ, ヨウイチ; イシカワ, マサヒロ /; MOTOYOSHI, Yoichi; ISHIKAWA, Masahiro; FRASER, Geoffrey L. (National Institute of Polar Research, 1995)
P(論文) Sapphirine-bearing silica-undersaturated granulites from Forefinger Point in Enderby Land, East Antarctica, preserve a variety of reaction textures suggestive of the prograde segment of the P-T evolution followed by nearly isothermal decompression. The granulites are composed of sapphirine, orthopyroxene, cordierite, garnet, spinel, corundum, K-feldspar, biotite and accessory zircon. Petrographical characteristics are i) spinel and corundum occur only as inclusions in sapphirine, ii) relict cordierite and biotite are included in the corundum, and iii) the sapphirine is locally in direct contact with porphyroblastic garnet, and the garnet is occasionally replaced by symplectitic intergrowth of orthopyroxene+sapphirine+cordierite±biotite. Chemographic relations in the FeO-MgO-Al_2O_3-SiO_2 system (FMAS), textural relations and chemical data indicate a clockwise P-T trajectory with marked decompression following peak conditions. departmental bulletin paper